Tocilizumab monotherapy after ultra-short glucocorticoid administration in giant cell arteritis: a single-arm, open-label, proof-of-concept study. (September 2021) - Christ, Lisa; Seitz, Luca; Scholz, Godehard; Sarbu, Adela-Cristina; Amsler, Jennifer; Bütikofer, Lukas; Tappeiner, Christoph; Kollert, Florian; Reichenbach, Stephan; Villiger, Peter M
Summary: Background: Two randomised controlled trials showed a glucocorticoid-sparing effect of tocilizumab in patients with giant cell arteritis. In the GUSTO trial we aimed to evaluate the efficacy and safety of tocilizumab monotherapy after ultra-short-term glucocorticoid treatment in patients with new-onset giant cell arteritis. Methods: This investigator-initiated, single-arm, single-centre, open-label, proof-of-concept trial with a Simon's two stage design was done at University Hospital Bern, Bern, Switzerland. We enrolled patients aged older than 50 years newly diagnosed with giant cell arteritis (within 4 weeks before the screening visit) satisfying the American College of Rheumatology criteria or with large vessel vasculitis-associated polymyalgia rheumatica. The participants received 500 mg methylprednisolone intravenously for 3 consecutive days. Thereafter, glucocorticoid treatment was discontinued and a single infusion of tocilizumab (8 mg/kg bodyweight) was administered intravenously, followed by weekly subcutaneous tocilizumab injections (162 mg) until week 52. The primary endpoint was the proportion of patients who had remission within 31 days and showed no relapse at week 24. The secondary endpoints were the proportion of patients with complete relapse-free remission of disease at weeks 24 and 52, and time to first remission, first relapse (after induction of remission), and first partial remission. This study is registered with ClinicalTrials.gov, NCT03745586 . Findings: From Nov 23, 2018, to Sept 22, 2019, 18 patients were enrolled (12 of 18 were female, 18 of 18 were White) with a median age of 72 (IQR 67–75) years. Overall, 15 of 18 patients had cranial symptoms, ten of 18 had polymyalgia rheumatica symptoms, and 13 of 18 showed a positive histopathology. At the interim analysis, three (25%) of 12 patients were in remission. The null hypothesis could not be rejected, and the study was futile with respect to the primary endpoint. However, 14 (78%) of 18 patients had remission within 24 weeks (mean time to first remission 11·1 weeks, 95% CI 8·3–13·9) and 13 of 18 showed no relapses up to 52 weeks (72%, 47–90). Mean time to first partial remission was 6·2 [3·7–8·7] weeks. Time to first relapse (after induction of remission) could not be estimated as there was no relapse after induction of remission. Overall, three of 18 patients did not respond to treatment and two of 18 discontinued the study due to an adverse event (hepatopathy [one] and diverticulitis [one]). Anterior ischaemic optic neuropathy occurred in one patient. Interpretation: The data show a slow remission-inducing and a lasting remission-maintaining effect of tocilizumab after an ultra-short pulse of glucocorticoids in patients with newly diagnosed giant cell arteritis. As a proof-of-concept study, our data do not allow us to propose clinical recommendations. Funding: Bern University Hospital, University of Bern, and F Hoffmann-La Roche.